Public Relations (PR) Crisis in the AI Era: The Threat of Digital Fraud Using Synthetic Video and Voice - Amalia Putri Setya Aryana; Nabil Surya Al Hakim; Dwi Novaria Misidawati (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of artificial intelligence (AI) in generating videos and mimicking voices presents both opportunities and new threats within the modern communication ecosystem. The ability of technologies such as deepfakes and voice cloning to create highly realistic content has triggered an increase in digital fraud, misinformation, and public manipulation. This study employs a descriptive qualitative method to thoroughly illustrate these phenomena through literature review, case content analysis, and observations of digital fraud trends on social media. The findings indicate that deepfake and voice-cloning technologies not only disrupt interpersonal communication but also have significant impacts on the Public Relations (PR) profession, particularly concerning reputation, public trust, and crisis management. The analyzed fraud cases demonstrate how fabricated content can infiltrate institutions, manipulate individuals, and disrupt decision-making processes. This study highlights the need for communication authentication protocols, PR–cybersecurity collaboration, and public education as mitigation efforts against AI-based fraud threats.